Comprehensive Analysis of N6-Methyladenosine-Related Long Noncoding RNA Prognosis of Acute Myeloid Leukemia and Immune Cell Infiltration - Zheng, Guowei; Liu, Mengying; Chang, Xinyu; Cao, Xiting; Dong, Ani; Zhu, Huili; Hu, Wanli; Xie, Junna; Zhao, Yang; Hu, Dongsheng; Jia, Xiaocan; Yang, Yongli; et al. (Frontiers in Genetics, 2022)
N6-methyladenosine related long noncoding RNAs play an essential role in many cancers’ development. However, the relationship between m6A-related lncRNAs and Acute Myelogenous Leukemia (AML) prognosis remains unclear. We systematically analyzed the association of m6A-related lncRNAs with the prognosis and tumor immune microenvironment features using the TARGET database. We screened 315 lncRNAs associated with the AML prognosis and identified nine key lncRNAs associated with m6A by LASSO Cox analysis. A model was established based on these nine lncRNAs, and the predictive power was explored in the TCGA database. The areas under the ROC curve of TARGET and TCGA database for ROC at 1, 3, and 5 years are 0.701, 0.704, 0.696, and 0.587, 0.639, 0.685, respectively. The nomogram and decision curve analysis (DCA) showed that the risk score was more accurate than other clinical indicators in evaluating patients' prognoses. The clusters with a better prognosis enrich the AML pathways and immune-related pathways. We also found a close correlation between prognostic m6A-related lncRNAs and tumor immune cell infiltration. LAG3 expression at the immune checkpoint was lower in the worse prognostic cluster. In conclusion, m6A-related lncRNAs partly affected AML prognosis by remodeling the TME and affecting the anticarcinogenic ability of immune checkpoints, especially LAG3 inhibitors. The prognosis model constructed with nine key m6A-related lncRNAs can provide a method to assess the prognosis of AML patients in both adults and children.